Peran Sistem Informasi Akuntansi Dalam Mengidentifikasi Dan Mencegah Kecurangan Pada Penyalahgunaan Akses Internal Perusahaan - Muhammad Riyan Dani; Erik Martua Simatupang; Arif Anakampun; Yolanda Pratiwi; Dea Natalia; Rivana Perangin-angin; Jufri Darma (Pusat Riset dan Inovasi Nasional, 2025)
Internal access abuse is a form of fraud that can significantly harm a company, both financially and reputationally. Therefore, it is essential for companies to implement effective preventive measures to protect the integrity of their information systems and assets. This article discusses various strategies that can be applied to prevent fraud, including the implementation of strong internal controls, segregation of duties, and strict access controls. Additionally, features such as audit trails, clear security policies, and the use of advanced security technologies are key elements in detecting and preventing access abuse. Building a culture of ethics and transparency within the company, as well as providing ongoing education and training to employees, is also crucial for raising awareness of fraud risks. Conducting regular audits and risk assessments can help companies identify potential weaknesses in their internal control systems. By adopting a comprehensive and integrated approach, companies can protect their assets, maintain operational integrity, and build trust among employees and stakeholders, ultimately contributing to the long-term success of the organization